Berbagai Konsep Hilal di Indonesia - Abu Yazid Raisal (University of Muhammadiyah Sumatera Utara, 2018)
The issue of the initial stipulation of the month (especially Ramadan, Shawwal and Zulhijah) in Indonesia to this day has not ended. One reason for the problem of defining the new moon. Admittedly in Indonesia there are a variety of views and opinions regarding the definition of the new moon which between one another seems contradictory. Nahdlatul Ulama defines the hilal to be visible (ruukyat), Muhammadiyah defines enough by reckoning, and the Ministry of Religion (Government) defines the possibility of being seen (let rukyat). Each of these views has advantages and disadvantages, and each of them has a syar'i's basic foundation and their respective knowledge.Keywords: Hilal, Beginning of The Month, Reckoning